2016
DOI: 10.1039/c6ay00725b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lead-free gunshot residue analogs

Abstract: Spectrochemical analysis and microscopy were used to identify statistically significant analytical markers present in simulated lead-free gunshot residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The method is relatively simple and can be considered almost nondestructive due to the small sample size required. In recent studies, LIBS was found to be very effective for glass and GSR analyses. ,, A nonspectroscopic technique which provides elemental composition is LA-ICPMS, which was shown by Almirall and Trejos to be propitious for the analysis of various materials …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is relatively simple and can be considered almost nondestructive due to the small sample size required. In recent studies, LIBS was found to be very effective for glass and GSR analyses. ,, A nonspectroscopic technique which provides elemental composition is LA-ICPMS, which was shown by Almirall and Trejos to be propitious for the analysis of various materials …”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, while LIBS was successful for pattern visualization, it should not be used as a replacement for SEM-EDX analysis. Fambro et al published two studies which investigated the potential for LIBS to be used for the analysis of GSR stemming from ammunition having lead-free composition. , They utilized LIBS in conjunction with SEM-EDX for both of these studies and emphasized the potential for LIBS to be used as a prescreening method before analysis using SEM-EDX. An example of the types of SEM-EDX maps used to correlate and compare with LIBS data in their 2017 study can be seen in Figure .…”
Section: Gunshot Residuementioning
confidence: 99%
“…reports in Ref. [ 43 ] the application of laser-induced breakdown spectroscopy to heavy-metal free GSR analysis by characterizing analogs of heavy-metal free GSR. They started from different material containing simulated primer compositions in order to mimic heavy-metal free primers.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of standard ammunition utilizes the compounds lead styphnate as the initiator, barium nitrate as the oxidant, and antimony sulfide as the fuel, all contained within the primer 1,7–8 . Therefore, standard IGSR elements, such as lead (Pb), barium (Ba), and antimony (Sb), are generated and then used to identify GSR.…”
Section: Introductionmentioning
confidence: 99%